MEDIA CULTURE AS A FACTOR OF SAFE DEVELOPMENT OF A MULTICULTURAL SOCIETY - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the problem of communication in intercultural society States policy of multiculturalism. The processes of globalization, accompanied by migration and the clash of cultures, actualize the problem of control over the media medium in order to prevent fire and interethnic conflicts.